Antiepithelial-Mesenchymal Transition of Herbal Active Substance in Tumor Cells via Different Signaling. (17th April 2020) - Cui, Xiaoji; Lin, Qinlu; Huang, Ping; Liang, Ying
Abstract : Epithelial-mesenchymal transition (EMT) is a biological process through which epithelial cells differentiate into mesenchymal cells. EMT plays an important role in embryonic development and wound healing; however, EMT also contributes to some pathological processes, such as tumor metastasis and fibrosis. EMT mechanisms, including gene mutation and transcription factor regulation, are complicated and not yet well understood. In this review, we introduce some herbal active substances that exert antitumor activity through inhibiting EMT that is induced by hypoxia, high blood glucose level, lipopolysaccharide, or other factors.